ARTISTIC IMAGERY AND CHARACTER TYPOLOGY IN LITERARY CRITICISM - Ma’diyeva Adiba Dovudovna (International Journal of Literature and Language Studies, 2026)
This article examines the theoretical, aesthetic, and epistemological foundations of artistic imagery (obraz) and imagery (obrazlilik) within literary criticism. By synthesizing insights from classical philosophy and Western aesthetics alongside Central Asian and Uzbek literary traditions, the study delineates the evolution of human representation from simple characterization (personaj) to complex characters (xarakter) and socially representative types (adabiy tip). Furthermore, it provides a comprehensive classification of artistic images according to creative methodology, literary genres, and structural organization within the literary text.